Mehrsprachigkeit im Fußball und mehrsprachige Wörterbücher der Fußballterminologie aus deutsch-polnischer Sicht - Taborek, Janusz (Dr. Kovač Verlag, 2012)
The article presents the history of football lexicography (with German and Polish) and the problems of multilingualism in the football. We discuss some problems of bilingual and multilingual dictionaries, e.g. non-alphabetical order, false friends, multi-word units etc.
Keywords: lexicography; language of sport; language of football; multilingualism